2017
DOI: 10.18554/refacs.v5i2.1709
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao consumo de medicamentos entre idosos de uma unidade básica de saúde

Abstract: O objetivo do estudo foi analisar o padrão de consumo de medicamentos entre idosos e fatores associados. Estudo transversal com 340 indivíduos com idade igual ou superior a 60, realizado em 2013. Os idosos que participaram deste estudo eram em sua maioria mulheres na faixa etária de 60 a 69 anos. A prevalência do uso de medicação foi de 99,7%. A polifarmácia (>5 medicamentos) ocorreu em 35,3% dos casos. As variáveis que apresentaram relação estatisticamente significativa com a quantidade de medicamentos foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
4
Order By: Relevance
“…Moreover, it is important to highlight that of the nine most frequent drug interactions found in the present study, six involved drugs classified by ATC as cardiovascular, agreeing with the findings of Somers et al 27 . The high frequency of coronary diseases and hypertension among the elderly 28 can explain the use of this medication class and consequently the greater risk of negative outcomes and interactions related to the cardiac system. It is therefore important to identify the medications, their impact and the risk of interactions in the context of frailty in order to promote health care among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to highlight that of the nine most frequent drug interactions found in the present study, six involved drugs classified by ATC as cardiovascular, agreeing with the findings of Somers et al 27 . The high frequency of coronary diseases and hypertension among the elderly 28 can explain the use of this medication class and consequently the greater risk of negative outcomes and interactions related to the cardiac system. It is therefore important to identify the medications, their impact and the risk of interactions in the context of frailty in order to promote health care among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Another Brazilian study, conducted in primarily low-income elderly people in the state of Rio Grande do Sul, found a prevalence of low adherence among a third of the 1,598 people interviewed. A third Brazilian study, in the state of Minas Gerais, found that adherence was 47% in 279 elderly participants, most of whom were low-income women on polypharmacy regimens 7,20,21…”
Section: Discussionmentioning
confidence: 99%
“…However, Brazilians tend to prefer pharmacological treatments, as they are easier to access, have a more evident therapeutic efficacy, and are simpler to take than making lifestyle changes. This difficulty in promoting lifestyle changes has been evidenced by low adherence to non-medication treatments as an auxiliary to pharmacological treatment 20,21,2330…”
Section: Discussionmentioning
confidence: 99%
“…Vicente e Santos 21 realizaram estudo com idosos do município de Rodeio (SC) e encontraram prevalência de utilização de medicamentos em 78% da população em estudo. Mosegui et al 22 Entretanto, a prevalência de utilização de medicamentos observada no presente estudo foi similar a prevalência observada em estudo realizado no município de São Paulo (SP) por Santos & Cunha 23 , que encontraram prevalência de utilização de medicamentos em 99,7% da população em estudo, com média de medicamentos consumidos por pessoa superior a observada neste estudo 4,24 , e com quantidade de pessoas em polifarmacoterapia inferior a verificada no presente estudo (35,3%).…”
Section: Discussionunclassified
“…Artigo originAl A grande prevalência no consumo de medicamentos observada no presente estudo talvez possa ser explicada pelo fato da população do estudo ser composta exclusivamente por idosas do sexo feminino, visto que maior utilização de medicamentos no sexo feminino foi verificada em outros estudos que analisaram o consumo entre homens e mulheres 4,7,23 . Muitos fatores podem estar associados com a grande prevalência no uso de medicamentos pela população idosa, como a grande quantidade de morbidades, tratamentos realizados por diversos profissionais diferentes e as políticas de acesso aos medicamentos 5 .…”
Section: /11unclassified